Multiple Nail Gun Penetrating Head Injury: A Case Report - SK, Sim; SC, Theophilus; AR, Noor Azman (IIUM Medical Journal Malaysia, 2013)
Intracranial nail gun injury is a rare subset of penetrating head injury. Here we report a case of intracranial nail gun injury in a Vietnamese patient who attempted suicide with no neurological deficit. Three nails were launched. Because the nail head acted as a brake, the launched nail could make a hole into the skull but could not entirely pass it. A rational management strategy should permit these patients to be discharged with no additional injury. Some medical and surgical management in penetrating head injury are discussed. The use of antibiotics and antiepileptic drugs and the retraction of the nail aided by the performance of a craniotomy surrounding the entry point are recommended.